With a little help from my friends: Supplying to multinationals, buying from multinationals, and domestic firm performance - Holger Görg; Adnan Seric (Kiel Institute for the World Economy (IfW), 2013)
This paper uses firm level data for 19 African countries to look at the link between domestic firms' business relationship with multinationals and their performance in terms of innovation and productivity. Quite uniquely, we also evaluate the importance of support received by the domestic firm, either from the government or the multinational business partner, for this link. Overall, our data analysis shows that for the average domestic firm, supplying to a foreign multinational in the country (the backward linkage) is positively associated with product innovation. Buying from a multinational (the forward linkage) is positively associated with labor productivity. These results are independent of any type of support from the government or multinationals. We also find that domestic firms' process innovation activity is only positively associated with supplying a multinational if the firm also receives assistance from the government or multinational. Furthermore, we find that supplying a multinational is only positively associated with domestic firms' productivity if the firm received technology transfer from the multinational customers.
Keywords: 330